Faktor-Faktor yang Mempengaruhi Manajemen Keselamatan Penerbangan: Faktor Manusia, Lingkungan Pengoperasian, dan Teknologi Pesawat Terbang - Andi Frianto Perangin Angin; Rifqi Raza Bunahri (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
Aviation safety management becomes more important to be considered because flight accidents can give a broader impact. Not only endangering its crews and passengers, but flight accidents also threaten people’s lives on the ground. This article then aims to explain the factors that influence aviation safety management. In the process, the authors use the qualitative research method by focusing on the literature review or studying the previous research. The result of this article shows that there are three factors that have an influence to aviation safety management. First, the human factor includes pilots, aviation operators, and other aviation staff. Second, operating space which includes weather conditions and the airport. Third, aircraft and its technologies which can be seen through good aircraft design and construction, as well as the technology that has a crucial role in aircraft operation.